Perspektif Hukum Internasional Terhadap Suku Bangsa Kurdi yang Stateless - Titalessy, Andre; Peilouw, Johanis Steny Franco; Rehatta, Veriana Josepha Batseba (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The background of this research is that citizenship is a form of identity that allows individuals to feel the meaning of ownership, rights and social obligations in the political community (state). The Universal Declaration of Human Rights (UDHR) confirms that everyone has the right to a citizenship.Purposes of the Research: Writing aims to determine the arrangement of International Law against a person who has no citizenship and to know the implementation of International Law against ethnic Kurds.Methods of the Research: This type of research is normative law, namely research that uses secondary data sources with data sources consisting of primary, secondary and tertiary legal materials. The data collection technique used was library research, namely research carried out by collecting various kinds of literary literature either through print media or online media with data collection tools in the form of document studies.Results of the Research: The results of this study indicate that international law has provided rules for a person who has no nationality, including the Universal Declaration of Human Rights, the 1954 Geneva Convention Concerning the Status of Stateless Persons and the 1961 Geneva Convention Concerning the Reduction of Statelessness, the Declaration on the Rights of Persons -Persons of National or Ethnic, Religious and Linguistic Minorities and the International Convention on the Elimination of All Forms of Racial Discrimination. International law has provided clear arrangements for resolving statelessness. But ethnic Kurds in Syria still do not enjoy citizenship rights. The participation of the state government is needed in tackling this.